2013
DOI: 10.1097/pgp.0b013e31826a62bb
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cytology in Serous and Endometrioid Endometrial Cancer

Abstract: The aim of this study was to determine the frequency of abnormal cervical cytology in preoperative cervical cytology of patients diagnosed with uterine papillary serous carcinoma (UPSC) and endometrioid endometrial carcinoma (EEC). In addition, associations between abnormal cervical cytology and clinicopathologic factors were evaluated. In this multicentre study, EEC patients diagnosed at two hospitals from 1999 to 2009 and UPSC patients diagnosed at five hospitals from 1992 to 2009, were included. Revision of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
(43 reference statements)
4
11
3
2
Order By: Relevance
“…In the subset of serous carcinomas, we found an equally high percentage of abnormal cervical cytology of 85.4% (41/48). The association of abnormal cervical cytology with advanced FIGO stage in our study was also demonstrated by Roelofsen et al, who observed a correlation of abnormal cervical cytology with cervical stromal invasion in endometrioid‐type endometrial carcinoma, and advanced stage in serous endometrial carcinoma. Also in our series there was a significant relation with abnormal cervical cytology and cervical stromal involvement.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the subset of serous carcinomas, we found an equally high percentage of abnormal cervical cytology of 85.4% (41/48). The association of abnormal cervical cytology with advanced FIGO stage in our study was also demonstrated by Roelofsen et al, who observed a correlation of abnormal cervical cytology with cervical stromal invasion in endometrioid‐type endometrial carcinoma, and advanced stage in serous endometrial carcinoma. Also in our series there was a significant relation with abnormal cervical cytology and cervical stromal involvement.…”
Section: Discussionsupporting
confidence: 89%
“…Also in our series there was a significant relation with abnormal cervical cytology and cervical stromal involvement. However, in contrast to Roelofsen et al, 22 we also found a correlation of abnormal cervical cytology with both disease‐specific and overall survival . This might be explained by the differences in study cohorts, since in our cohort all histological types were included, whereas Roelofsen et al only included patients with endometrioid and serous‐type endometrial carcinoma.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Roelofsen et al showed that abnormal endometrial cells on cytology may be found more commonly in patients with USC, than in patients with endometrioid carcinoma, where this is rare. 23 In accordance with other authors, LVSI, the depth of myometrial invasion and tumour size were not significantly associated with a poor prognosis in USC. 24,25 In our study, more than half of the USCs coexisted with at least one other subtype of uterine cancer (endometrioid, clear cell and mucinous).…”
Section: Discussionsupporting
confidence: 88%